A quartz crystal microbalance study of the adsorption of benzene and acetone vapors onto coumarin-substituted manganese phthalocyanine film - Can Omur, Birsel; Altindal, Ahmet (Tubitak Scientific & Technological Research Council Turkey, 2017)
A novel coumarin-substituted manganese phthalocyanine (5) was successfully synthesized and used as sensing element for benzene and acetone vapor detection. The effects of water vapor on the benzene and acetone vapor-sensing properties and adsorption isotherms on thin film of 5 were also studied. Our preliminary results indicated that the presence of humidity modifies the baseline frequency but not the sensitivity of the sensor toward benzene and acetone vapors. Two isotherm models, Langmuir and Jovanovic isotherms, were selected to describe the adsorption process. Linear regression analysis, which is the most basic and commonly used predictive analysis method, was used to estimate the suitability of the selected isotherm models. The Jovanovic model was found to be adequate for describing benzene and acetone adsorption onto compound 5.
Keywords: VOC sensing; adsorption isotherm; frequency shifts; phthalocyanine; SENSING PROPERTIES; Physics